Perceptions of male circumcision among married couples in rural Malawi - Shacham, Enba; Godlonton, Susan; Thornton, Rebecca L. (SAGE Publications, 2014)
Voluntary medical male circumcision (VMMC) is being suggested as an essential HIV prevention strategy in high-prevalence areas. These analyses reflect data collected from 360 married couples, 50% of which included a circumcised husband and the other 50% uncircumcised, in rural Malawi. Regardless of their circumcision status, men were more likely to perceive that being circumcised was less painful than having a tooth pulled, giving birth, and having malaria. Men reported having the same sexual pleasure regardless of the circumcision status, while women were 2.0 times more likely to report greater sexual pleasure with a circumcised partner. Participants identified the medical benefits of VMMC and highlighted the potential personal benefits of VMMC. As VMMC has become a promising method of HIV prevention, this study revealed opportunities for intervention development to increase rates of VMMC among men.